The Role of Agriculture in Economic Growth: A Comparison of Mediterranean and Northern Views in Europe - Ioanna Apostolidou; Achilleas Kontogeorgos; Anastasios Michailidis; Efstratios Loizou (International Journal of Economic Sciences and Applied Research, 2014)
The main objective of this paper is to identify the causal relationship that exists between agricultural value added per worker and Gross Domestic Product per capita in Europe. More specifically, the role of agriculture in economic growth is examined with special emphasis to the differences and similarities among Mediterranean and Northern countries. In order to examine short-run and long-run relationships, recent methods of linear co-integration are employed while the role of agricultural value added in economic growth is also examined by Granger causality tests. Results show a bi-directional relationship between agricultural value added and economic growth in the northern EU countries and only in one Mediterranean country. From a policy point of view, this relationship is of crucial importance since it can facilitate successful economic decisions. Taking into consideration that the role of agriculture in economic growth is an issue that always attracts the interest of scholars, this research could be prove extremely interesting and useful. Especially for this period of economic crisis, when the whole growth approach is reexamined and reevaluated, the research findings provide evidence that agriculture can lead as an engine of growth in several EU countries and can play stabilizer's role in the whole EU economy.
Keywords: F15; F43; O13; 330; Agricultural value-added; GDP; Causality; Co-integration